Featured Article: Caregiver Perceptions of Stress and Sibling Conflict During Pediatric Cancer Treatment. (21st February 2018) - Fladeboe, Kaitlyn; King, Kevin; Kawamura, Joy; Gurtovenko, Kyrill; Stettler, Nicole; Compas, Bruce; Friedman, Debra; Lengua, Liliana; Breiger, David; Katz, Lynn Fainsilber
Abstract: Objective: The current study examined the effect of stress on sibling conflict during the first year of pediatric cancer treatment. Method: Families ( N = 103) included a child with cancer (aged 2–17 years, M age = 6.46, SD = 3.52) and at least one sibling aged <5 years of the child with cancer ( M age = 8.34, SD = 5.61). Primary caregivers completed monthly questionnaires throughout the first year of treatment assessing five sources of stress (i.e., general life, cancer-related, financial, perceived treatment intensity, and life threat) and level of sibling conflict. Using multilevel modeling, we explored the effects of these stressors on conflict both at the within- and between-family levels to examine if changes in stress resulted in concurrent changes in conflict within an individual family, and whether greater average stress affected the trajectory of conflict between families, respectively. Results: At the between-family level, higher average levels of cancer-related stress, general life stress, and financial stress were associated with higher sibling conflict at the end of the first year of treatment. Perceived treatment intensity and life threat were not associated with conflict. No stressors were associated with conflict at the within-family level. Conclusions: During pediatric cancer treatment, some stressors may spill over into family relationships and contribute to increases in sibling conflict.